2010
DOI: 10.1002/joc.2257
|View full text |Cite
|
Sign up to set email alerts
|

Exceedance of heat index thresholds for 15 regions under a warming climate using the wet‐bulb globe temperature

Abstract: Thermal comfort is quantified in 15 regions using the wet-bulb globe temperature (WBGT), examining past and future rates of thresholds exceedance corresponding to moderate, high, and extreme heat (28, 32, and 35°C, respectively). As recent changes to thermal comfort appear to be dominated by temperature and humidity, a WBGT approximation based only on these is used. A new homogenised dataset from 1973 to 2003 is developed which provides WBGT daily means, daily maximums averaged over 5-day periods, and the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
213
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(227 citation statements)
references
References 46 publications
10
213
0
4
Order By: Relevance
“…Sherwood and Huber (2010) proposed that heat stress imposes an upper bound on how much global warming humans can adapt to, since with large global warming, T w in some regions can approach levels (35°C) that should induce hyperthermia in humans. Willett and Sherwood (2012), in a study of past and future-projected WBGT trends in 15 regions, found positive historical trends in almost all regions studied. Their statistical model suggested that, assuming a uniform 2°C warming above present levels, a 35°C WBGT threshold would be exceeded during at least some extreme events in almost all 15 regions.…”
Section: Introductionmentioning
confidence: 90%
“…Sherwood and Huber (2010) proposed that heat stress imposes an upper bound on how much global warming humans can adapt to, since with large global warming, T w in some regions can approach levels (35°C) that should induce hyperthermia in humans. Willett and Sherwood (2012), in a study of past and future-projected WBGT trends in 15 regions, found positive historical trends in almost all regions studied. Their statistical model suggested that, assuming a uniform 2°C warming above present levels, a 35°C WBGT threshold would be exceeded during at least some extreme events in almost all 15 regions.…”
Section: Introductionmentioning
confidence: 90%
“…The continuous rise of absolute humidity in the lower troposphere has also been reported in many regions which add substantial implications for human thermal comfort and heat-related mortality and morbidity. In particular, this may add substantial risk in already humid countries, where a small increase in temperature can have profound consequences on heat stress 9) .…”
Section: Current Statusmentioning
confidence: 99%
“…temperature humidity index, physiological equivalent temperature, wet-bulb globe temperature and urban thermal field variance index (UTFVI). (Kakon, Nobuo, Kojima, & Yoko, 2010;Matzarakis, Mayer, & Iziomon, 1999;Willett & Sherwood, 2012;Zhang, 2006). Among these indices, UTFVI is the most widely used index for the ecological evaluation of urban environment due to its direct relation to LST (Alfraihat, Mulugeta, & Gala, 2016;Li et al, 2013;Liu & Zhang, 2011;Mackey, Lee, & Smith, 2012;Nichol, 2005).…”
Section: Introductionmentioning
confidence: 99%